Młodzi wyborcy jako audytorium „dyskursu zmiany” w 2015 roku - Marzęcki, Radosław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
W niniejszym artykule autor spogląda na kampanię wyborczą w 2015 roku (zarówno prezydencką, jak i parlamentarną) przez pryzmat różnych stylów retoryki, którymi posługiwały się partie polityczne. W czasach zmediatyzowanej polityki, która organizowana jest w ramach kampanii o charakterze permanentnym, rywalizacja toczy się przede wszystkim poza formalnymi instytucjami, głównie w przestrzeni medialnej. Na poziomie retorycznym ujawnia się konflikt dwóch dyskursów: „dyskursu zmiany” (retoryka progresywna), kreowanego przez partie opozycyjne oraz „dyskursu kontynuacji” (retoryka konserwatywna), będącego sposobem politycznej komunikacji partii rządzących. Celem artykułu jest analiza opinii polskich studentów w ważnych kwestiach społecznych i politycznych oraz próba identyfikacji tej grupy wiekowej obywateli w kategoriach „elektoratu zmiany”. Wnioski z analizy powinny być pomocne w wyjaśnianiu przyczyn wysokiego poziomu poparcia udzielanego przez młodych wyborców partiom opozycyjnym.

This article focuses on the election campaigns in 2015 (both presidential and parliamentary) in the context of the various rhetoric styles applied by the political parties. In times of the mediatization of politics and permanent campaigns political competition is primarily taking place outside formal institutions, having moved into the sphere, first and foremost, of the mass media. This reveals a conflict of two discourses at the level of political rhetoric: on the one hand it is a ‘discourse of change’ (progressive rhetoric) created by the opposition parties and, on the other hand, ‘a discourse of continuity’ (conservative rhetoric), which seems to be the means of political communication used by the ruling parties. The main purpose of the article is an analysis of Polish students’ opinions on important social and political issues and an attempt to define this age group in terms of the ‘electorate of change’. The conclusions should be helpful in explaining the reasons for the high level of support given to opposition parties by young voters in Poland.
Young Voters as an Audience of the ‘Discourse of Change’ in 2015
Keywords: młodzież; youth; dyskurs polityczny; political discourse; retoryka progresywna; progressive rhetoric; retoryka konserwatywna; conservative rhetoric; zmiana; change